Salut :)
D=(2x - 1)(x - 5)+(2x - 1)²
développer et réduire
D=(2x - 1)(x - 5)+(2x - 1)²
D = 2x x (x) + 2x x (-5) - 1 x (x) - 1 x (-5) + (2x)² - 2 x 2x x 1 + 1²
D = 2x² - 10x - 1x + 5 + 4x² - 4x + 1
D = 6x² - 15x + 6
factoriser
D=(2x - 1)(x - 5)+(2x - 1)²
D = (2x - 1)(x - 5) + (2x - 1)(2x - 1)
D = (2x - 1)[(x - 5) + (2x - 1)]
D = (2x - 1)(3x - 6)
calculer D quand x vaut (- 3)
D=(2x - 1)(x - 5)+(2x - 1)²
D = (2x - 1)(3x - 6)
D = (2 x (-3) - 1)(3 x (-3) - 6)
D = (-6 - 1)(-9 - 6)
D = -7 x (-15)
D = 105
J'espère t'avoir aidé(e)! :)